Estimation of the Growth Rate in Fetuses With an Abnormal Cerebroplacental Ratio Compared to Those With Suspected Growth Restriction Without Evidence of Centralization of Blood Flow. (1st May 2015) - Regan, Jodi; Masters, Heather; Warshak, Carri R.
Abstract : Objectives: To evaluate the growth rate in fetuses with suspected growth restriction according to their Doppler characteristics. Methods: A retrospective cohort of fetuses with suspected growth restriction was identified. We reviewed umbilical artery and middle cerebral Doppler pulsatility indices and calculated the cerebroplacental ratio. Three study groups were determined: (1) normal umbilical artery Doppler findings; (2) abnormal umbilical artery findings with a normal cerebroplacental ratio; and (3) abnormal umbilical artery findings with an abnormal cerebroplacental ratio. The primary outcome was the growth rate as estimated by fetal biometry from serial sonographic evaluations. Analysis of the mean growth rate in each study group was performed by analysis of variance. In addition, linear regression analysis comparing the cerebroplacental ratio to the growth rate was performed. Results: Fetal growth restriction was suspected in 416 patients; 176 patients were included in this analysis: 113, 38, and 25 in groups 1, 2, and 3 respectively. The estimated mean (SD) growth rate in group 3 was significantly lower than in groups 1 and 2: 8.3 (4.4) versus 19.6 (6.0) and 18.6 (7.7) g/d, respectively ( P < .001). Linear regression analysis revealed a strong correlation between the growth rate and cerebroplacental ratio ( r = 0.76; R 2 = 0.58) as well as the birth weight and cerebroplacental ratio ( r = 0.78; R 2 = 0.61). Conclusions: In fetuses with suspected growth restriction and abnormal umbilical artery Doppler findings, an abnormal cerebroplacental ratio is strongly associated with reduced fetal growth. In contrast, if the cerebroplacental ratio is normal, even in the setting of abnormal umbilical artery Doppler findings, fetuses grow similarly to those with normal umbilical artery findings.